A microcontroller for in situ single‐crystal diffraction measurements with a PILATUS‐2M detector under an alternating electric field. Issue 3 (1st June 2017) - Choe, Hyeokmin; Heidbrink, Stefan; Ziolkowski, Michael; Pietsch, Ullrich; Dyadkin, Vadim; Gorfman, Semën; Chernyshov, Dmitry
Abstract : A new data acquisition system is proposed for in situ single‐crystal diffraction with a pixel area detector under an alternating electric field. Abstract : A new data acquisition system for in situ time‐resolved three‐dimensional reciprocal space mapping is reported. The system is based on a programmable microcontroller for generating a functional low‐voltage signal, a pixel area detector serving as a master clock and a high‐voltage amplifier. Both Bragg and diffuse scattering can be mapped in a large volume of reciprocal space under an alternating electric field of a pre‐programmed shape. The system has been tested at the Swiss–Norwegian Beamline BM01 of the European Synchrotron by measuring the electric field dependence of diffuse X‐ray scattering from a functional perovskite‐based ferroelectric single crystal.